Kiss of midnight eaudiobook - Adrian, Lara (Midnight Breed, 2010)
He watches her from across the crowded dance club, a sensual black-haired stranger who stirs Gabrielle Maxwell's deepest fantasies. But nothing about this night—or this man—is what it seems. For when Gabrielle witnesses a murder outside the club, reality shifts into something dark and deadly. In that shattering instant she is thrust into a realm she never knew existed—a realm where vampires stalk the shadows and a blood war is set to ignite. Lucan Thorne despises the violence carried out by his lawless brethren. A vampire himself, Lucan is a Breed warrior, sworn to protect his kind—and the unwitting humans existing alongside them—from the mounting threat of the Rogues. Lucan cannot risk binding himself to a mortal woman, but when Gabrielle is targeted by his enemies, he has no choice but to bring her into the dark underworld he commands. Here, in the arms of the Breed's formidable leader, Gabrielle will confront an extraordinary destiny of danger, seduction, and the darkest pleasures of all.